Peningkatan Perilaku Hidup Bersih dan Sehat (PHBS) melalui Edukasi dan Pelatihan Cuci Tangan Pakai Sabun (CTPS) pada Masyarakat Kelurahan Sei Pematang Pasir - wahidah wahidah; Nila Sari; Zata Ismah; Khoiro Futri Ayumi (Universitas Pahlawan Tuanku Tambusai, 2026)
Clean and Healthy Living Behavior (CHLB) is a promotive and preventive approach to improving public health, one of which is through proper Handwashing with Soap (HWWS). However, the implementation of correct HWWS practices remains suboptimal among residents of Sei Pematang Pasir Village. This community service program aimed to enhance community knowledge and practical skills regarding CHLB through education and HWWS training. The methods included observation, interviews, interactive health education, demonstrations, hands-on practice, and evaluation using pre-tests, post-tests, and observation sheets. The results demonstrated significant improvements in participants’ knowledge of CHLB, the benefits of HWWS, critical times for handwashing, and the six-step handwashing technique. Participants also showed better practical skills in performing HWWS according to World Health Organization (WHO) recommendations, particularly in using soap, cleaning between the fingers, thumbs, fingertips, and rinsing hands properly. These findings indicate that combining health education with demonstrations and practical training effectively improves community knowledge, skills, and CHLB practices, thereby contributing to the sustainable prevention of infectious diseases and promoting better public health outcomes.